أساطير بلاد الرافدين و الاغريق - وفاء , محمد , تواتي طليبة (جامعة الوادي University of eloued, 2018)
نظرا لما للأساطير من تاثير واضح على حياة الشعوب، فقد عملت كل مجموعة بشرية في سياق تطورها التاريخي على تجسيد تجربتها حسب الوسط البيئي الذي عاشت فيه، وحسب انفتاحها على حياة الامم والشعوب الاخرى، ومن تلك الشعوب بلاد الرافدين وبلاد الاغريق، وانه من خلال معالجتنا لموضوع البحث يمكننا الوقوف عند بعض النتائج التي يمكن تلخيصها في ما يلي : ان الاسطورة على رغم من اختلاف تعريفاتها فهي حكاية مقدسة تروي قصة تقليدية ابطالها الآلهة وانصاف الآلهة، والتي تهدف الى تاسيس طقوس البشر من فعل وفكر وادب ، وتجيب عن كل تساؤلات الإنسان القديم حول الكون ومن يحكمه من الالهة، وقصص الموت والحياة والفناء والخلود ... ومن خلال دراسة النصوص الأسطورية للسومريين والبابليين يتضح أن النشأة الأولى للكون من المياه ، التي تمثلت (نمو) عند السومريين وعند البابليين (تيامات وابسو) ، ومن هذه الكتلة المائية انبثق الآلهة ، والذي يمكن اعتباره بداية التنظيم. اما المرحلة الثانية تمثلت في بداية تكاثر الآلهة على الطريقة البشرية ، وهو ما تم تاكيده من طرف العلماء والباحثين وقد ادى الاختلاف في القوى بين الآلهة العتيقة التي وصفت بالتنظيم والفئة المسببة للصخب والفوضى والصراع بين الآلهة ، وكان لزاما انتصار آلهة على الأخرى حتى يتم تنظيم الكون وخلق الإنسان وهو امر منطقي عند الانسان الرافدي الذي يهدف للراحة والسكينة وتنظيم الحياة. نجد ايضا نوع من الصراع في القصص الطوفان السومري والبابلي فالبشر لم يحققوا الغاية التي وجدوا من اجلها، وبالتالي غضب الآلهة وقرارها انهاء امر البشر ، وهو الامر الذي نجده عند (جلجامش) الذي خلد اسمه وطغيانه ووفاءه وبطولته ورحلته نحو الخلود ، ونجده ايضا في ملحمتي (ايتانا وادابا) واحدهما كان يبحث عن الانجاب ليستمر نسله وضيع الآخر فرصته في الخلود، وقد جمعت الآلهة (عشتار) بين الخصب الحب والزواج بسيطرتها على الخصب الحياة من نبات وحيوان، ورغبتها بالسيطرة على عالم الأموات وبنزولها للعالم الاسفل. اما عن المثيولوجيا الاغريقية فقد اعطت لمحة عن الفكر اليوناني القديم من خلال التفاصيل الدقيقة ونشاة الكون وعناصره وعن اله وانسابه ونسله ، وكيفية خلق الكون والانسان، والتي توحي الى تقديس الاغريقي القديم لقوى الطبيعة المحيطة به، فكانت الاسطورة هي اول خطوة خطاها نحو الابداع والاكتشاف , وبالتدريج تكونت عنده حكايا مختلفة تمثلت في ملاحم كاملة حول الالهة والابطال , التي تحولت فيما بعد الى ملحمتي الالياذة والاوديسة المشهورتين في العالم القديم , واللتان ترويان حضارة مدينة طروادة , وهما مصدر الهام كل الادباء عبر العصور."In view of the fact that legends have a clear impact on the lives of peoples, each human group has worked in the context of its historical development to reflect its experience according to the environment in which it lived and its openness to the lives of nations and other peoples, including Mesopotamia and the countries of the Greeks. Research We can stand by some of the results that can be summarized in the following: The legend, despite its different definitions, is a sacred story that tells the story of the traditional heroes of the gods and the halves of the gods, which aims to establish the rituals of human beings of the act, thought and literature, and answer all the questions of the ancient man about the universe and who governs of the gods, and stories of death and life and eternity and eternity ... Through the study of the mythical texts of the Sumerians and Babylonians, it is clear that the first creation of the universe was water, represented by the growth of the Sumerians and the Babylonians (Tiamat and Abso). The second stage was the beginning of the multiplication of the gods in the human way, which was confirmed by scientists and researchers. The difference in power between the ancient gods, which was described by the organization and the category causing the chaos, chaos and conflict between the gods, and the victory of gods on the other until the universe was organized and created Man, which is logical in man Rafidi, which aims to rest and tranquility and organization of life. We find also a kind of conflict in the stories of the Sumerian and Babylonian flood. Humans did not achieve the end for which they were found, and therefore the wrath of the gods and their decision to end the matter of men. This is what we find at Gilgamesh, whose name, tyranny, loyalty, heroism and journey to eternity, (Ishtar) between the fertile love and marriage control of fertile life of plant and animal, and its desire to control the world of the dead and descent to the world below. As for the Greek mythology, it gave a glimpse of ancient Greek thought through the precise details and the creation of the universe and its elements, the gene, its genealogy and its descendants, and how to create the universe and man, which suggests the ancient Greek sanctification of the forces of nature surrounding it. The legend was the first step towards innovation and discovery. He had a variety of stories about the gods and the heroes, which later turned into the famous Elias and Odyssey of the ancient world, and which inspired the civilization of the city of Troy and inspired all writers throughout the ages.
دراسة مقارنة
مذكرة ماستر تاريخ تخصص تاريخ الحضارات القديمة
Keywords: بلاد الرافدين , بلاد الاغريق , الاساطير; La Mésopotamie, pays des Grecs, légendes; Mesopotamia, the country of the Greeks, legends